2004
DOI: 10.1152/ajprenal.00439.2003
|View full text |Cite
|
Sign up to set email alerts
|

Membrane organization and function of M1 and M23 isoforms of aquaporin-4 in epithelial cells

Abstract: (AQP4) water channels exist as heterotetramers of M1 and M23 splice variants and appear to be present in orthogonal arrays of intramembraneous particles (OAPs) visualized by freeze-fracture microscopy. We report that AQP4 forms OAPs in rat gastric parietal cells but not in parietal cells from the mouse or kangaroo rat. Furthermore, the organization of principal cell OAPs in Brattleboro rat kidney is perturbed by vasopressin (arginine vasopressin). Membranes of LLC-PK1 cells expressing M23-AQP4 showed large, ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

15
145
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 142 publications
(162 citation statements)
references
References 43 publications
15
145
2
Order By: Relevance
“…Water permeability studies showed that the M1 isoform conducts water at a higher rate than the M23 isoform (4,6). Quantitative immunoblotting and immunofluorescence studies showed that expression of AQP4 M1 was 8-fold higher than expression of M23 (7). On the contrary, Hirt et al (8) observed higher expression of M23 mRNA levels in mouse brain.…”
Section: Micrornas (Mirnas)mentioning
confidence: 97%
See 1 more Smart Citation
“…Water permeability studies showed that the M1 isoform conducts water at a higher rate than the M23 isoform (4,6). Quantitative immunoblotting and immunofluorescence studies showed that expression of AQP4 M1 was 8-fold higher than expression of M23 (7). On the contrary, Hirt et al (8) observed higher expression of M23 mRNA levels in mouse brain.…”
Section: Micrornas (Mirnas)mentioning
confidence: 97%
“…Expression of M1 is possibly crucial in cerebral homeostasis as its single channel water permeability rates are much higher than M23. Furthermore, M23 is often implicated with structural organization of the membrane (7,22).…”
Section: Mir-130a Represses Transcriptional Activity Of Aqp4 M1mentioning
confidence: 99%
“…Freezefracture electron microscopy of cells transfected with AQP4-M23 shows large OAPs, sometimes containing Ͼ100 particles, whereas OAPs are largely absent in cells transfected with AQP4-M1 (33). OAP size is reduced when AQP1-M1 is coexpressed with AQP4-M23, suggesting an interaction between these two isoforms in vivo (21,33).…”
Section: Aquaporin-4 (Aqp4)mentioning
confidence: 98%
“…The single-channel water permeability of M23 is approximately 8 times greater than that of M1, likely due to the ability of M23 to form stable square arrays. 118 It has been further suggested that the larger the array, the more it is able to accommodate a higher water flux through the membrane induced by an osmotic gradient, consistent with the speculation that AQP4 could play an adhesive role at gap junctions. 48 At the end-foot cellular membrane near the perivascular space, the anchoring of AQP4 requires a-syntrophin, a member of the dystrophin complex.…”
mentioning
confidence: 54%
“…46 Silberstein et al found that a phosphomimetic M23-Ser 111E forms 2.5-times larger square arrays compared with wild-type M23 and possesses a 1.5-fold increase in single-channel water permeability. 118 However, Assentoft et al did not find an increase in water permeability in oocytes transfected with AQP4 with a phosphomimetic Ser 111 site or in oocytes transfected with AQP4 and treated with protein kinase A (PKA) or PKG activators. 9 They also did not detect evidence of Ser 111 phosphorylation in vivo after treating animals with an mGluR1/5 analog.…”
mentioning
confidence: 98%